(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2005)
Nowadays mining industry is considered as one of key branches of economy of the Republic of Armenia. Under circumstances of transition from planned economy to market one, over-appraising of the value of the deposits is required and dictated. As to the deposit of Armanis, the exploitation system should be revised, which at the moment doesn’t promote and contribute to profitable utilization. The central part of the afore-mentioned deposit is assumed to exploit via quarrying, which will make possible and cause the curtailing of expenditures for both mining and maintenance of costly underground mountainous yields in operation.